(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Recently many adult female specimens of Lissorhoptrus orywphilus Kuschel, 1952 were collected in Western Lombardy (Northern Italy) both ibernant under Calluna vulgaris L. (January-March) and then moving on grasses and sedges, mainly on Carex acutiformis Ehrh. (April), near rice fields. This species, which is now recorded for the first time for Europe, is an important pest of rice, Oryza sativa L., in North America, but is also known from Mexico and Cuba; moreover partenogenetic populations have been introduced into Japan, North and South Korea, and China, where it is now seriously damaging rice cultivations. The adult of L. oryzophilus can be identified as follows: medium-sized (length 3.3-3.7 mm rostrum included), elongate-oval; integument reddish brown, densely clothed with contiguous to imbricated scales and waterproof coating; on dorsum scales usually light brown at side and dark brown medially; rostrum thick, with scrobes in lateral view oblique; antennae with funicle 6-segmented and with first segment of club glabrous; midtibiae bladelike, with evenly strongly curved outer margin and with dense elongate swimming hairs on inner and outer margins. In Europe these characters allow to distinguish this taxon from other species of Erirhinidae as well as from Bagous Germar, 1817, an aquatic genus of Curculionidae which shares L. oryzophilus in the general habitus. Besides, some notes on know biology of the species are reported.